Proceedings of the 2016 International Symposium on Code Generation and Optimization 2016
DOI: 10.1145/2854038.2854046
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting recent SIMD architectural advances for irregular applications

Abstract: A broad class of applications involve indirect or datadependent memory accesses and are referred to as irregular applications. Recent developments in SIMD architectures-specifically, the emergence of wider SIMD lanes, combination of SIMD parallelism with many-core MIMD parallelism, and more flexible programming APIs-are providing new opportunities as well as challenges for this class of applications. In this paper, we propose a general optimization methodology, to effectively optimize different subclasses of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…For stripe splitting mode, we need to run a lock-based code for tiles in the same stripe as we mentioned before. In SIMD-level, as opposed to previous efforts based on a heavy data reorganization preprocessing [11], we rely on the built-in conflicts detection intrinsics provided by Xeon Phi to dynamically address the possible update conflicts.…”
Section: Update Conflictmentioning
confidence: 99%
See 2 more Smart Citations
“…For stripe splitting mode, we need to run a lock-based code for tiles in the same stripe as we mentioned before. In SIMD-level, as opposed to previous efforts based on a heavy data reorganization preprocessing [11], we rely on the built-in conflicts detection intrinsics provided by Xeon Phi to dynamically address the possible update conflicts.…”
Section: Update Conflictmentioning
confidence: 99%
“…GraphPhi focuses on a different throughputoriented architecture and explores many unique features that are not shown on GPUs. There are also some optimization techniques for Xeon Phi [6,11,22]. Although they comprehensively explore advanced SIMD execution, none of them offer a general graph processing framework by effectively exploiting both MIMD and SIMD execution, or emerging HBM techniques.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Green‐Marl is a domain specific language for graph processing. Chen et al proposed compiler optimization methodology for graph and other irregular applications on Intel Xeon Phi coprocessors. Ahn et al developed a customized processing‐in‐memory (PIM) accelerator for large‐scale graph processing.…”
Section: Related Workmentioning
confidence: 99%
“…al. propose a general optimization technique for data-parallel problems with indirect memory accesses [1], by viewing the problem as a sparse matrix computation. Yavors'kii and Weigel identified that tiled computations, such as the ones found in spin systems, are greatly improved by re-organizing the memory in blocks [12].…”
Section: Related Workmentioning
confidence: 99%